2008
DOI: 10.1002/jor.20674
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tissue cytokines and chemokines increase with repetitive upper extremity tasks

Abstract: We investigated inflammation in rats performing a low repetition, negligible force (LRNF) or high repetition, negligible force (HRNF) task of reaching and retrieving food pellets at target rates of two or four reaches/min for 2 h/day, for 6-8 weeks. Serum was assayed for 11 cytokines and chemokines; forelimb tissues for four cytokines. Macrophages were counted in forelimb tissues of LRNF rats to add to results from our previous studies of HRNF rats. In HRNF rats, serum IL-1a, IL-1b, TNFa, MIP2, MIP3a, and RANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
112
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(139 citation statements)
references
References 35 publications
26
112
1
Order By: Relevance
“…In the repetitive rat model, localized inflammation occurs immediately in bone and joint tissues and remains elevated for 5 or 12 weeks, depending on the level of inducing injury 27 . The inflammatory response was matched by exposure-dependent structural changes in the skeletal tissues, such as adaptive bone remodelling with performance of a low-force task but degradative bone and cartilage changes with a highforce task 27,28 . When ibuprofen treatment, at anti-inflammatory levels, was administered early during the inflammatory period, a reduction in inflammatory cytokines was observed in the loaded joint tissues 27 .…”
Section: Biochemical and Biomechanical Interventions After Joint Traumamentioning
confidence: 99%
“…In the repetitive rat model, localized inflammation occurs immediately in bone and joint tissues and remains elevated for 5 or 12 weeks, depending on the level of inducing injury 27 . The inflammatory response was matched by exposure-dependent structural changes in the skeletal tissues, such as adaptive bone remodelling with performance of a low-force task but degradative bone and cartilage changes with a highforce task 27,28 . When ibuprofen treatment, at anti-inflammatory levels, was administered early during the inflammatory period, a reduction in inflammatory cytokines was observed in the loaded joint tissues 27 .…”
Section: Biochemical and Biomechanical Interventions After Joint Traumamentioning
confidence: 99%
“…Evidence of tissue injury was paralleled by inlammatory responses, such as increased pro-inlammatory cytokines in lexor digitorum muscles and tendons [30][31][32]39], and increased macrophages in the median nerve at the level of the wrist (Figure 3A, B). Elevated levels of key pro-inlammatory cytokines, IL-1beta, and TNF-alpha were also observed in serum of rats that had performed a HRHF task for 12 weeks (12-week HRHF rats) ( Figure 3D, E).…”
Section: Ibuprofen Efectively Reduced Tissue Inlammation Induced By Tmentioning
confidence: 97%
“…Those suggested maximum limits are indicated in Table 1. 4. An operant rat model of WMSD Several animal models have been developed to study WMSDs and have shown that repetitive hand activities induce sensorimotor dysfunction [27][28][29][30][31][32][33]. A model developed in our laboratory is a unique operant rat model of voluntary reaching and grasping (Figure 1; [7,34]).…”
Section: Ibuprofenmentioning
confidence: 99%
See 2 more Smart Citations